Arabidopsis PCH2 Mediates Meiotic Chromosome Remodeling and Maturation of Crossovers - Lambing, Christophe (PLoS Genet, 2015)
Meiotic chromosomes are organized into linear looped chromatin arrays by a protein axis localized along the loop-bases. Programmed remodelling of the axis occurs during prophase I of meiosis. Structured illumination microscopy (SIM) has revealed dynamic changes in the chromosome axis in Arabidopsis thaliana and Brassica oleracea. We show that the axis associated protein ASY1 is depleted during zygotene concomitant with synaptonemal complex (SC) formation. Study of an Atpch2 mutant demonstrates this requires the conserved AAA+ ATPase, PCH2, which localizes to the sites of axis remodelling. Loss of PCH2 leads to a failure to deplete ASY1 from the axes and compromizes SC polymerisation. Immunolocalization of recombination proteins in Atpch2 indicates that recombination initiation and CO designation during early prophase I occur normally. Evidence suggests that CO interference is initially functional in the mutant but there is a defect in CO maturation following designation. This leads to a reduction in COs and a failure to form COs between some homologous chromosome pairs leading to univalent chromosomes at metaphase I. Genetic analysis reveals that CO distribution is also affected in some chromosome regions. Together these data indicate that the axis remodelling defect in Atpch2 disrupts normal patterned formation of COs.